Analysis of the Legal Framework for Combatting Human Trafficking in Kenya - Katungati, Sabastian Muthuka (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
Human trafficking remains a critical issue in Kenya, serving as a source, transit, and destination country for trafficking victims. Despite various legal initiatives, including the enactment of the Counter-Trafficking in Persons Act of 2010, the persistence of human trafficking indicates significant gaps in the country's legal and enforcement mechanisms. This study offers a comprehensive analysis of Kenya's current legal framework, identifying critical deficiencies that undermine efforts to combat human trafficking effectively. Through a qualitative research methodology, including document analysis and case studies, the study explores how effective Kenya is the in the field of anti-trafficking laws and in combating human trafficking. The findings underscore substantial weaknesses in enforcing these laws, largely due to systemic corruption, insufficient resources, and a lack of sufficient specialized training among law enforcement agencies. Additionally, the research highlights the socio-economic and cultural factors that exacerbate the vulnerability of specific groups, particularly women and children, to trafficking. These factors, coupled with inadequate victim protection measures, hinder the effectiveness of Kenya's legal framework in addressing the root causes of human trafficking. The study concludes by offering targeted recommendations for strengthening Kenya's legal response to human trafficking. These include enhancing victim protection services, imposing stricter penalties on traffickers, allocating more resources to enforcement agencies, and fostering better coordination among stakeholders, including government, local civil society, and international partners. By addressing these issues, Kenya can significantly improve its efforts to combat human trafficking, safeguard the rights of victims, and fulfill its international obligations under the Palermo Protocol.